Effect of multi-structured zinc oxide on the electrical properties of polypropylene insulating materials. (5th July 2017) - Zha, Jun-Wei; Cheng, Qi; Yan, Hong-Da; Li, Wei-Kang; Dang, Zhi-Min
Abstract: In this paper, polypropylene (PP) nanocomposites filled with ZnO nanoparticles, nanowires and tera-needle-like whiskers were prepared by a melt blending method. The effects of multi-structure ZnO fillers on space charge, breakdown strength and electrical conductive current of PP nanocomposites were investigated. The nanocomposites presented a remarkable suppression on space charge by adding ZnO nanowires, while the addition of ZnO nanoparticles and tera-needle-like whiskers did not effectively suppress the space charge accumulation. The electrical field distortion occurred in the inner of the PP filled with ZnO nanoparticles and tera-needle-like whiskers were about 1.8 kV mm −1 and 3.3 kV mm −1, respectively. Compared with pure PP, the breakdown strength of the PP nanocomposites filled with ZnO nanoparticles and nanowires increased, while they decreased in PP nanocomposites filled with tera-needle-like ZnO whiskers. This work indicated that the improvements on the electrical properties, especially the charge transport and space charge suppression in the nanocomposites were closely related to the different structure of ZnO.